Phytoarchitecture for buildings based on photosynthetic pathways to combat volatile organic compounds - Ganjar Samudro; Harida Samudro; Dwi Rinnarsuri Noraduola; Sarwoko Mangkoedihardjo; Azzah Nazihah Che Abdul Rahim (Institute of Advanced Engineering and Science, 2026)
Volatile organic compounds (VOCs) originating from construction materials and human activities present considerable health hazards in indoor settings. Phytoarchitecture provides a sustainable approach by incorporating vegetation into architectural design to effectively mitigate pollutants. This research seeks to define criteria for plant positioning according to photosynthetic pathways (C3, C4, and crassulacean acid metabolism (CAM)) to optimize VOC absorption. Employing a systematic literature review methodology, data on plant physiology, and leaf morphology were examined to establish a design framework. The findings suggest that the positioning of plants should be based on their stomatal opening cycles: CAM plants, which absorb carbon dioxide at night, are optimal for indoor bedrooms, whereas C3/C4 plants are more appropriate for daytime active areas and outdoor facades. Additionally, plants exhibiting narrow leaf profiles and elevated stomatal density exhibit enhanced VOC removal efficacy. It was determined that synchronizing architectural design with plant photosynthetic cycles establishes an efficient, passive air purification system that improves both indoor environmental quality (IEQ) and building aesthetics.